2018
DOI: 10.1007/s10753-018-0762-2
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Aquaporins (AQP1 and AQP5) and Na,K-ATPase in Porcine Reproductive and Respiratory Syndrome Virus-Infected Pig Lungs

Abstract: Aquaporins (AQPs) and Na,K-ATPase control water transport across the air space-capillary barrier in the distal lung and play an important role in the formation and resolution of lung edema. Porcine reproductive and respiratory syndrome virus (PRRSV) infection usually causes pulmonary inflammation and edema in the infected pig lungs. To investigate the possibility that PRRSV infection may cause altered expression of AQPs and Na,K-ATPase messenger RNA (mRNA) levels and protein expression of AQP1, AQP5, and Na,K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…AQP5 is known to be mostly correlated with abnormal gland secretion in airway. Recent studies have supported the notion that the protein levels of AQP1 and AQP5 are decreased in inflammatory states [38,39]. Consistent with these, we observed that the protein levels of AQP1 and AQP5 were lower in the lung tissues of allergic mice than in normal control.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…AQP5 is known to be mostly correlated with abnormal gland secretion in airway. Recent studies have supported the notion that the protein levels of AQP1 and AQP5 are decreased in inflammatory states [38,39]. Consistent with these, we observed that the protein levels of AQP1 and AQP5 were lower in the lung tissues of allergic mice than in normal control.…”
Section: Discussionsupporting
confidence: 91%
“…AQP5, together with AQP1, is the primary route for osmotic water transport between the capillary and the airspace [38,39], and is fundamental to lung water transport and normal lung function [44]. AQP1 is critically related to lung edema and involved in many inflammatory diseases [45–47].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, AQP-mediated fluid movement is regulated by an osmotic gradient 21 . To provide a basis for understanding the role of AQP5 in transepithelial ion transport, we examined whether these solute transporters modulate volume regulation of AQP5 in the salivary glands.…”
Section: Resultsmentioning
confidence: 99%
“…Water absorption through AQPs is driven by an osmotic gradient that is generated by transcellular Na + transport. Apical Na + entry in surface-absorptive cells of the colonic epithelium is mediated by the ENaC, and basolateral Na + exit is mediated through the Na + -K + -ATPase, sodium transporters that were identified in the mammalian colon and lung at the mRNA and protein levels 31,52 . We found the ENaC and Na + -K + -ATPase distribution in the colonic epithelium, small intestinal villus epithelium, gastric pit and fundic gland, implying the roles of these transporters in Na + absorption in the colon and small intestinal villus epithelium 31 .…”
Section: Discussionmentioning
confidence: 99%